Association between body roundness index and osteoarthritis: a cross-sectional analysis of NHANES 2011–2018 - Liang, Huazheng; Si, Wenyue; Li, Lin; Yang, Kaiying (Frontiers in Nutrition, 2024)
Objective The objective of this study was to investigate the potential association between body roundness index (BRI) and the risk of osteoarthritis (OA) in US adults. Methods A cross-sectional analysis consisting of 20,232 participants was conducted using data from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2018. Participants (≥20 years of age) were included and divided into OA and non-OA groups. Then, the demographics and characteristics of the participants were compared between the two groups. The relationship between BRI and OA was assessed using a multivariate logistic regression model with fitted smoothed curve techniques. Additionally, subgroup analyses on the correlation between BRI and OA were performed. Results The BRI scores in OA group were significantly higher than in the non-OA group (6.60 ± 2.62 vs. 5.46 ± 2.34, p < 0.001). Multivariate logistic analysis revealed that a significantly positive association between BRI and OA (OR = 1.12, 95% CI: 1.09–1.14, p < 0.001). In the subgroup analysis, only the race subgroup showed a significant difference between BRI and OA (p < 0.001). Conclusion Our findings highlight a significantly positive association between BRI and OA prevalence in the general US population.